The Influence of the Finance and Logistics Departments of the OSIS at SMA Labschool Kebayoran on the Managerial and Entrepreneurial Skills of Members - Anandasha Parameswara (CV. Publikasi Indonesia, 2026)
OSIS plays a pivotal role in shaping students' leadership and organizational skills, and the Finance and Logistics Departments, being integral to managing resources for various student activities, offer practical experiences that are believed to enhance these skills. This research examined the influence of the Finance and Logistics Departments of the OSIS (Intra-School Student Organization) at SMA Labschool Kebayoran on members' managerial and entrepreneurial skills during the 2024–2025 period. A survey using a Likert scale questionnaire was distributed online via Google Forms to active members of these departments, employing purposive sampling and descriptive statistical analysis to quantify responses. The results revealed strong agreement among respondents (77.8%–88.9% strongly agreed) that involvement enhanced managerial competencies such as decision-making, strategic planning, interpersonal communication, and team influence, while entrepreneurial skills improved through practical experiences such as sponsor sourcing, vendor management, risk-taking, and innovation (55.6%–88.9% agreement). Supporting factors included school guidance and intermember cooperation, whereas inhibiting factors encompassed time constraints, funding challenges, and limited experience. Overall, participation in these departments significantly fostered leadership, professionalism, and an entrepreneurial mindset among high school students, positioning OSIS as a vital platform for skill development.